2019
DOI: 10.1103/physrevb.100.165421
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculation of field emission from metal surfaces with atomic-scale defects

Abstract: In this work we combine density functional theory and quantum transport calculations to study the influence of atomic-scale defects on the work function and field emission characteristics of metal surfaces. We develop a general methodology for the calculation of the field emitted current density from nano-featured surfaces, which is then used to study specific defects on a Cu(111) surface. Our results show that the inclusion of a defect can significantly locally enhance the field emitted current density. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Notice the variation found in the local work function, field emission factor, and the emission area with the voltage range. These deductions are consistent with the finding of Toijala et al [30], who used density functional theory (DFT) and quantum transport calculations to demonstrate the effect of an atomic-level surface imperfection on the bulk work function of copper (4.76 eV). Accordingly, the lowering of the work function occurs locally by 0.32 eV with an adatom and 0.51 eV with a pyramid defect present at the (111) surface, leading thereby to a significant increase in the field emission current.…”
Section: Emission Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…Notice the variation found in the local work function, field emission factor, and the emission area with the voltage range. These deductions are consistent with the finding of Toijala et al [30], who used density functional theory (DFT) and quantum transport calculations to demonstrate the effect of an atomic-level surface imperfection on the bulk work function of copper (4.76 eV). Accordingly, the lowering of the work function occurs locally by 0.32 eV with an adatom and 0.51 eV with a pyramid defect present at the (111) surface, leading thereby to a significant increase in the field emission current.…”
Section: Emission Characteristicssupporting
confidence: 90%
“…Accordingly, the operational parameters like work function, field enhancement factor, and the effective emission area vary with the bias. Toijala et al [30] emphasized the importance of atomic-level defects at the emitter tip and observed reduction of the work function (e.g., from the bulk value of 4.76 eV by 0.32 or 0.51 eV in copper). Interpretation of I-V data poses significant challenges in case of 1D nanowires, as many emission parameters extracted and reported in the literature are physically unrealistic.…”
Section: Introductionmentioning
confidence: 99%
“…al., on copper (100) surface have shown a significant effect on the work function due to microstructures [46]. An ab initio computational method has been developed to calculate the field-emitted current from defective metal surfaces by combining the density functional theory and electronic structure calculations with quantum transport methods on copper (111) surface by Toijala [47]. However, from this model, it is difficult to justify the effective high value of the field enhancement factor in the field emission characteristics of a metal surface, as observed in their as well as our present experiments.…”
Section: Discussion On Existing Theories On Ion-irradiated Structure Formation and Field Emission Studiesmentioning
confidence: 99%
“…(c) Investigating the effect of single-atom adsorption and single-atom-defects on otherwise flat surfaces (e.g. [139]). (d) Investigating the electrostatics and emission properties of atomically sharp emitters, such as those developed by Fink [140], and of the three-atom tips used in gas field ion sources for scanning ion microscopy (e.g.…”
Section: Atomistic Electrostatic Modellingmentioning
confidence: 99%